Root cause analysis of liner collapse and crack of bi-metal composite pipe used for gas transmission. (February 2022) - Zhang, Shuxin; Ma, Qianzhi; Xu, Changfeng; Li, Lifeng; Wang, Mingfeng; Zhang, Zhe; Wang, Shuai; Li, Lei
Highlights: This paper determines root cause analysis of liner collapse and crack of bi-metal composite pipe used for gas transmission. The external pressure test showed that the Φ168 liner collapse under the pressure of 1.76 MPa which is lower than the calculated value. The root cause of the crack of the liner is bending fatigue, and the load originates from pressure fluctuations during operation. The carbon steel pipe with regular pigging was recommended for this application situation. Abstract: An underground gas storage company adopted bimetallic composite pipes for gas transmission. The pipelines were inspected with industrial camera, it was found that a large number of pipelines had liner collapsed, and some of collapsed liner had suspected cracks. In order to analyze the reasons for the collapse and cracking of the liner, visual inspection, non-destructive testing, material examination, crack analysis, bend fatigue test and pressure test were conducted. The results showed that the material properties of the bimetal composite pipe meet standard requirements. The external pressure test was imposed on Φ168 composite pipe, the liner collapse under the pressure of 1.76 MPa which is lower than the calculated value. The cause of collapse was analyzed from manufacturing process and service condition. There are micro-cracks around the main crack of the liner, the fracture showed fatigue striations and thickness thinning characteristic. The root cause of the liner collapse is that the water enters the interlayer during the manufacturing of bimetallic composite pipe, and the thermal expansion coefficient of base pipe and lining pipe is different. When external anti-corrosion coating was manufactured and temperature changed during operation, collapse tendency of the liner increased. The root cause of the crack of the liner is bending fatigue, and the load originates from pressure fluctuations during operation. In order to avoid such incidents, the online inspection should be performed for the effusion part of the pipeline to check whether the remaining wall thickness of the base pipe meets the requirements for safe operation. The carbon steel pipe with regular pigging was recommended for this application situation.